Impact of Work-School Conflict to Employee Performance: Moderation of Perception Organizational Support and Work Characteristics - Mafizatun Nurhayati; Asep Rokhyadi Permana Saputra; Awan Santosa; Shinta Rahmani; Eny Ariyanto (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: This study aims to analyze the role of perceived organizational support and job characteristics in the effect of work-school conflict on employee performance.Methodology: The population of this study is employees who work in several agencies in Jakarta, who are also master’s degree students in private universities which are excellence accredited, located in region of Jakarta, with a total sample of 275 respondents. The data analysis was conducted through Partial Least Square-Structural Equation Model (PLS-SEM).Finding: The results showed that work-school conflict has a negative effect on employee performance. Perceived organizational support has a positive effect on employee performance. This study found that organizational support was not able to weaken the effect of work-school conflict on employee performance in employees who were also students. Job characteristics have a positive effect on employee performance.Conclusion: The condition of a person playing multiple roles can cause stress, busy activities, and disturbances that have an impact on sub-optimal performance. Employees believe that the organization cares for and supports them, which is shown fairly in the decisions taken, the existence of good rewards, good working conditions, and support from superiors that will improve employee performance. Variation in skills, task identity, task autonomy, and feedback can affect employee performance, because the greater the diversity of work activities carried out, the more meaningful a person will feel. If a worker who is also a student is not able to manage the role conflict between work and school, the job characteristics will not be able to reduce the conflict, and it will impact to the decrease of employee performance.